Pathogenetic mechanisms of destructive pneumonia in children. Case report with literature review - E.M. Tolstova; M.V. Besedina; O.V. Zaitseva; N.S. Zaitseva; S.B. Yatsyshina; D.V. Khaspekov; E.B. Olkhova; I.V. Turishchev; N.A. Sholokhova; P.P. Galeev; T.Yu. Belyaeva (LCC «Medicine-Inform», 2023)
E.M. Tolstova1, M.V. Besedina1, O.V. Zaytseva1, N.S. Zaitseva1, S.B. Yatsyshina2, D.V. Khaspekov3, E.B. Olkhova1,3, I.V. Turishchev3, N.A. Sholokhova3,4, P.P. Galeev3, T.Yu. Belyaeva3 1A.I. Yevdokimov Moscow State University of Medicine and Dentistry, Moscow, Russian Federation 2Central Research Institute of Epidemiology of the Russian Federal Service for Supervision of Consumer Rights Protection and Human Well-Being, Moscow, Russian Federation 3St. Vladimir Children's City Clinical Hospital, Moscow, Russian Federation 4Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation Destructive pneumonia (DP) in children is a complication derived from community-acquired pneumonia, while parenchymal necrosis occurs in the pulmonary infiltration zone with the formation of multiple merging small cavities. The disease pathogenesis has not yet been precisely established. The factors predisposing to pulmonary destructive complications in pneumonia remain unknown. We present a case study of this disease in a 5-year-old female patient hospitalized in December 2022. Manifestation in the form of acute upper respiratory tract infection, subsequent deterioration with the progression of pneumonia and pleurisy indicate the importance of viral-bacterial interactions in the DP pathogenesis. Influenza A was confirmed in the laboratory, while Streptococcus pneumoniae was isolated in the fluid culture obtained during bronchoalveolar lavage. Using the example of the presented case, we discuss the mechanisms of DP pathogenesis in children from a modern perspective. The necessity of coagulology, a combination of radiology diagnostic methods (radiography, ultrasound, computed tomography) was justified. It is necessary to further study the pathogenetic mechanisms of the DP progression in order to optimize preventive and therapeutic rehabilitation measures in community-acquired pneumonia in children. Keywords: destructive pneumonia, necrotizing pneumonia, influenza A, Streptococcus pneumoniae, hypercoagulation. For citation: Tolstova E.M., Besedina M.V., Zaytseva O.V., Zaitseva N.S., Yatsyshina S.B., Khaspekov D.V., Olkhova E.B., Turishchev I.V., Sholokhova N.A., Galeev P.P., Belyaeva T.Yu. Pathogenetic mechanisms of destructive pneumonia in children. Case report with literature review. Russian Journal of Woman and Child Health. 2023;6(3):310-319 (in Russ.). DOI: 10.32364/2618-8430-2023-6-3-15.